Social interaction between principals and teachers in urban and rural schools and the influence on generation Alpha’s learning engagement: A comparative thematic study - Rahmiwati, Rahmiwati; Sulisworo, Dwi; Hartanto, Dody (Edelweiss Applied Science and Technology, 2025)
This study examines how social interactions between principals and teachers in urban and rural schools influence the learning engagement of Generation Alpha students and how these dynamics support equitable, technology-enabled learning aligned with Sustainable Development Goals (SDGs). A systematic literature review and bibliometric analysis were conducted using the Dimensions database (2020–2025), following PRISMA procedures to identify studies on leadership collaboration, contextual school differences, and student engagement. VOSviewer was used to map keyword networks and thematic patterns. The findings show a steady increase in publications and citations, indicating rising scholarly interest in principal–teacher collaboration. Such interactions enhance teacher motivation, strengthen school climate, and encourage digital and student-centered pedagogies suited to Generation Alpha. Urban schools generally depend on structured systems and technology-supported communication, while rural schools emphasize relational trust and community-based leadership. Despite these differences, both contexts highlight the importance of adaptive collaboration in promoting engagement and reducing disparities. Effective principal–teacher interaction supports digital integration, relational trust, and inclusive practices, linking classroom-level improvements with broader systemic reforms that advance SDG 4 (Quality Education), SDG 10 (Reduced Inequalities), and SDG 17 (Partnerships). The study recommends context-sensitive leadership, strategic use of digital tools, and stronger professional learning communities to improve engagement across school settings.